2023
DOI: 10.1136/jitc-2022-006127
|View full text |Cite
|
Sign up to set email alerts
|

First-line nivolumab plus ipilimumab for metastatic non-small cell lung cancer, including patients with ECOG performance status 2 and other special populations: CheckMate 817

Abstract: BackgroundCheckMate 817, a phase 3B study, evaluated flat-dose nivolumab plus weight-based ipilimumab in patients with metastatic non-small cell lung cancer (NSCLC). Here, in this research, we report on first-line treatment in patients with Eastern Cooperative Oncology Group (ECOG) performance status (PS) 0–1 (cohort A) and special populations (cohort A1: ECOG PS 2; or ECOG PS 0–1 with untreated brain metastases, renal impairment, hepatic impairment, or controlled HIV infection).MethodsCohorts A and A1 receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Our univariate analysis of the total population showed a similar trend, though multivariate analysis through Cox regression with forward stepwise (likelihood ratio) showed that this variable failed to step in the risk factor model, which might be attributed to the small sample size of the present study. But after literatures investigation about the optimal timing of immunotherapy [34,35] and the potential impact of EGFR-TKI on tumor microenvironment [36,37], we prone to believe that the earlier treatment of immunochemotherapy after EGFR-TKI resistance, the better therapeutic effect would be observed. Besides, Cheng et al discovered that for EGFR-TKI-resistant NSCLC patients, immunochemotherapy was more effective in young patients without T790M, liver metastasis, and brain metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Our univariate analysis of the total population showed a similar trend, though multivariate analysis through Cox regression with forward stepwise (likelihood ratio) showed that this variable failed to step in the risk factor model, which might be attributed to the small sample size of the present study. But after literatures investigation about the optimal timing of immunotherapy [34,35] and the potential impact of EGFR-TKI on tumor microenvironment [36,37], we prone to believe that the earlier treatment of immunochemotherapy after EGFR-TKI resistance, the better therapeutic effect would be observed. Besides, Cheng et al discovered that for EGFR-TKI-resistant NSCLC patients, immunochemotherapy was more effective in young patients without T790M, liver metastasis, and brain metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study suggested that dual ICI therapy was well tolerated but associated with inferior outcomes in this population of patients, likely due to poor prognosis associated with the underlying disease. 75 Although these studies improve our knowledge of the safety and efficacy of ICI therapy in patients with advanced age, poor performance status, and significant comorbidity remains an unmet need. Creating stronger evidence-based recommendations to inform treatment of these special population of patients is challenging and requires a broader representation of this population in pivotal clinical trials.…”
Section: Special Population (Multiple Chronic Conditions Poor Perform...mentioning
confidence: 99%
“…There is paucity of prospective data to guide the optimal treatment of advanced cancer in patients with poor performance status (ECOG 2-3) or advanced age ≥70 years), highlighting the importance of shared decision making regarding implementation of guideline-recommended care. 1,58 These special populations of patients are often routinely excluded or underrepresented from clinical trials but recently published data from three prospective RCTs 73,74,75 has evaluated the safety and efficacy of single agent and combination immune checkpoint inhibition in this patient population. The IPSOS study is a phase III, global, randomized trial that evaluated first line anti-PD-L1 therapy with atezolizumab versus single agent chemotherapy (vinorelbine or gemcitabine) in investigator-determined platinum ineligible, EGFR/ALK-mutation negative advanced NSCLC with poor performance status (ECOG 2-3) or advanced age (≥70 years) with good performance status (ECOG 0-1) but substantial comorbidities or contraindications to platinum doublet therapy.…”
Section: Special Population (Multiple Chronic Conditions Poor Perform...mentioning
confidence: 99%
“…Treatment of NSCLC with ICI produces long-lasting survival and durable responses; however, responses are not seen in the majority of patients. Response rates of 19–45% are reported in patients treated with anti-PD-1 [ 7 10 ], and 18–36.4% with the combination of anti-CTLA-4 with anti-PD-1 [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%